Diagnosis and Treatment of Wedge-Shaped Defects of Hard Dental Tissues - Nariman, Aliyev Agil; Yagub, Gurbanov Ramin; Azad, Gurskaya Narmina (American Journal of Biology and Natural Sciences, 2025)
A wedge-shaped defect is considered a non-carious lesion of the tooth because it is not caused by cariogenic microflora. Until recently, there was no unified theory explaining the origin of this condition. The restoration of dental tissues with such defects presents certain difficulties, as it requires a special approach to cavity preparation and treatment, as well as a correct choice of filling material. It is also necessary to take into account systemic diseases that can influence the process of hard tissue loss.